Nathan for you. The complete series. [videorecording (DVD)] (Comedy Central / Paramount, 2018)
Experience all four seasons of Nathan Fielder's entrepreneurial genius as he provides real small businesses with strategies no traditional consultant would dare attempt. From the infamous gas rebate excursion to the grand opening of Dumb Starbucks to the epic feature-length series finale, "Finding Frances". This 9-disc set also includes never-before-seen footage, deleted scenes, and brand-new audio commentary